A Proposed Method for Key Frame Extraction - Hadi Ali, Israa; T. Al – Fatlawi, Talib (International Journal of Engineering and Technology, 2018)
Video structure analysis can be considered as a major step in too many applications, such as video summarization, video browsing, content-based video indexing,and retrieval and so on. Â Video structure analysis aims to split the video into its major components( scenes, shots, keyframes).Â A key frame is one of the fundamental components of video; it can be defined as a frame or set of frames that give a good representation and summarization of whole contents of a shot. It must contain most of the features of the shot that it represented. In this paper, we proposed an easy method for key frame extraction from the videoâ€™s shot. In the first step of the proposed system, the frames are divided (hashed) into groups (buckets) based on cosine distance, in this step the frame is converted to HSV color space, and angle between frame is computed, the frames that have similar angle are going the same bucket. In the second step, from each groupkeyframe is selected, the results we get can be considered good and reasonable.Â Â